Student suggestions for addressing heavy episodic drinking. Issue 2 (8th March 2022) - Meister, Shawna R.; Barker, Bryce; Flores-Pajot, Marie-Claire
Abstract: Objective This study examines student suggestions for other students, campuses, and society to address heavy episodic drinking (HED) and associated harms. Participants: Included 110 post-secondary students (27 males, 83 females), ages 17 to 30 years, from five universities across four Canadian provinces. Method: Purposeful sampling was used to screen in participants who drank in excess of Canada's Low-Risk Alcohol Drinking Guidelines. As part of a larger study, focus groups were held with qualifying students examining HED behaviors, suggestions and potential barriers to addressing HED among post-secondary students. Results: Suggestions included providing earlier education on harms, receiving messages from respected peers and adults, and teaching how to drink in moderation. Barriers included peer pressure, not knowing own limits, and post-secondary drinking culture. Conclusions: Campuses might not be using the most effective methods to reduce HED, may be facing unknown barriers, and need to understand perspectives of students in order to reduce HED.